Traffic and highway engineering - Garber, Nicholas J. (Cengage Learning, 2010)
Gives students insight into various facets of traffic and highway engineering. This work begins with a discussion of the pivotal role transportation plays in our society, including employment opportunities, historical impact, and the impact of transportation on our daily lives. It also focuses on specific issues facing transportation engineers.